ANALYSIS OF DIGITAL TECHNOLOGY ON DA'WAH COMMUNICATION STRATEGIES IN THE MODERN ERA - Hsb, Akmal Rizki Gunawan; Gunawan, Syahrul; Kartika, Resti Okvani; Anggraeni, Nur Najmi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2025)
The use of social media and digital platforms is increasing in da’wah activities. Many studies have not explored the optimal use of technology by da’wah practitioners to reach wider and more diverse audiences or face digital challenges, such as disinformation, the digital divide, and technical skills. This research explores the influence of digital technology on da’wah communication strategies in the modern era using the case study method—data collection through in-depth interviews, participant observation, and analysis of documentation from various digital platforms. Research findings show that social media, video platforms, and podcasts have changed the way preachers preach, allowing preachers to reach a wider and more diverse audience with more interesting and interactive content. In addition, the use of analytical tools to understand audience demographics is very important in increasing the effectiveness of message delivery. However, challenges such as the digital divide and the need for technical skills in content creation were also identified. The results of this research emphasize the need for preachers to receive digital skills training so that messages can be conveyed professionally and attractively. In addition, this research provides practical recommendations for preachers to optimize the use of technology in da’wah activities, including content creation strategies and how to deal with challenges such as misinformation.